Antibacterial effectiveness meets improved mechanical properties: Manuka honey/gellan gum composite hydrogels for cartilage repair. (15th October 2018) - Bonifacio, Maria A.; Cometa, Stefania; Cochis, Andrea; Gentile, Piergiorgio; Ferreira, Ana M.; Azzimonti, Barbara; Procino, Giuseppe; Ceci, Edmondo; Rimondini, Lia; De Giglio, Elvira
Highlights: Composite hydrogels based on gellan gum and Manuka honey have been prepared. The addition of halloysite nanotubes improves gel compressive modulus up to 143 kPa. Hydrogels inhibit the proliferation of S. aureus and epidermidis clinical isolates. Chondrogenesis of human stem cells seeded on the gels was successfully achieved. The developed gel composites could be an innovative tool for cartilage repair. Abstract: Biomaterials for cartilage repair are still far from clinical requirements, even if several studies recently focused on this topic. In this respect, Nature-derived hydrogels are a promising class of scaffolds for cartilage tissue engineering, mimicking the native cellular microenvironment. However, they frequently lack mechanical features required for cartilage applications and are commonly subjected to infection threat. This work describes the innovative use of Manuka honey as molecular spacer for preparing gellan gum-based composites with intrinsic antibacterial properties and superior compressive Young's modulus in respect of several Nature-derived gels based on chitosan, hyaluronic acid or alginate. The addition of Manuka honey made hydrogels able to inhibit the proliferation of S. aureus and S. epidermidis clinical isolates. Furthermore, no cytotoxic effects were detected on human mesenchymal stem cells seeded on the hydrogels. Moreover, chondrogenesis experiments showed a consistent expression of collagen II and high synthesis of GAGs and proteoglycans, thus indicating the formation of cartilage matrix. Overall, these data suggest that the developed smart composites have a great potential as tools for cartilage tissue engineering.